Composite material, preparation method of solution of composite material, light-emitting device and preparation method of light-emitting device

By doping organic materials with halogen and using high dielectric constant solvents to form stable nanoparticle dispersions, the problems of agglomeration and performance limitations in light-emitting devices are solved, and high-performance functional film preparation is achieved, simplifying the preparation of high-performance functional films The process is reduced and the use of toxic substances is reduced.

CN119307253APending Publication Date: 2025-01-14GUANGDONG JUHUA PRINTING DISPLAY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310849615.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the prior art, it is difficult to prepare stable nanoparticles of organic materials, resulting in limited performance of functional film layers of light emitting devices, and often toxic solvents or a large number of subsequent purification steps are required to reduce the surfactant content.

Method used

By doping organic materials with halogen, the agglomeration of organic material nanoparticles is inhibited by using halogen to form stable nanoparticles, and a high dielectric constant anti-solvent is used to promote charge transfer and separation to form a stable nanoparticle dispersion for use in the form of a stable nanoparticle dispersion. Inkjet printing prepares the functional film layer of the light emitting device.

Benefits of technology

The photoelectric performance of the light emitting device is improved, the preparation process is simplified, the dependence on toxic solvents and surfactants is reduced, and the stability and performance of the film layer is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307253A_ABST
    Figure CN119307253A_ABST
Patent Text Reader

Abstract

The invention relates to a composite material, and the composite material comprises an organic material, and the organic material is doped with halogen. The invention also relates to a preparation method of a solution of the composite material, a light-emitting device and a preparation method of the light-emitting device. According to the scheme provided by the invention, the organic material nanoparticles are doped with halogen, so that agglomeration of the organic material nanoparticles can be inhibited, the organic material nanoparticles are stabilized, and the composite material is beneficial to preparation of ink containing the stable organic material nanoparticles; the performance of a light-emitting device can be improved when the material is used for preparing a functional film layer of the light-emitting device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of organic light emitting diodes, and more specifically, to a composite material, a method for preparing a solution of the composite material, a light emitting device, and a method for preparing the light emitting device. Background Art

[0002] Existing light-emitting devices are mainly prepared by inkjet printing and evaporation. Compared with evaporation, inkjet printing has the advantages of simple process, ability to prepare large-size devices and low cost. When the functional film layer of a light-emitting device is prepared by printing, it is necessary to prepare the ink of the corresponding functional film layer in advance, and then set the ink in the corresponding pixel to complete the preparation of the functional film layer. For example, in the organic light-emitting diode (OLED) manufacturing process, the inkjet printing method is used to inject the corresponding functional material ink into the pixel unit to prepare the hole injection layer (HIL), hole transport layer (HTL), light-emitting layer (EML), etc.

[0003] For light-emitting devices based on organic materials, the solution processability of organic materials is crucial when making the ink required for inkjet printing based on solution processing. One way to achieve this is through molecular engineering design, such as modifying the conjugated main chain of the organic material with a long alkyl chain to improve its solubility in organic solvents, but this will affect the photoelectric properties of the organic material to a certain extent, and usually requires the use of toxic solvents such as halogenated solvents or aromatic solvents to improve the solubility of organic materials in solvents, which will limit the multi-layer deposition of functional film layers of organic materials. Another way is to prepare nanoparticle dispersions of organic materials, thereby freeing the solution processing of organic materials from their solubility requirements for solvents, reducing to a certain extent the requirements for orthogonal solvent systems for multi-layer deposited organic material layers, and the preparation of nanoparticle dispersions of organic materials can rely less on molecular engineering. However, the colloidal stability of nanoparticle dispersions prepared in this way is poor. Only very few organic materials show sufficient inherent colloidal stability. Most organic materials will undergo strong agglomeration during the preparation of nanoparticle dispersions, making it impossible to further process the nanoparticle dispersions. Even if surfactants are introduced as stabilizers to obtain stable nanoparticle dispersions, a large number of subsequent purification steps are required to reduce the final surfactant content when making the functional film layer of the light-emitting device. Otherwise, these surfactants will remain in the functional film layer of the light-emitting device, limiting the performance of the organic light-emitting device. Summary of the invention

[0004] In view of this, the embodiment of the present application provides a composite material to solve the problem that it is difficult to make stable nanoparticles from organic materials in the prior art, resulting in limited performance of the prepared functional film layer. On this basis, a method for preparing a solution of the composite material, a light-emitting device, and a method for preparing the light-emitting device are provided.

[0005] In a first aspect, an embodiment of the present application provides a composite material, wherein the composite material includes an organic material, and the organic material is doped with halogen.

[0006] In a second aspect, an embodiment of the present application further provides a method for preparing a composite material solution, the method comprising:

[0007] mixing an organic material with a first solvent to obtain a first solution;

[0008] Dissolving a halogen element in a second solvent to obtain a second solution containing the halogen;

[0009] mixing the first solution and the second solution to obtain an organic material solution doped with halogen;

[0010] The organic material solution and a third solvent are mixed to obtain a solution of the composite material.

[0011] In a third aspect, an embodiment of the present application further provides a light-emitting device, the light-emitting device comprising:

[0012] a first electrode and a second electrode;

[0013] The light-emitting layer is disposed between the first electrode and the second electrode, and the light-emitting layer is prepared based on the composite material mentioned above, or is prepared based on a solution of the composite material prepared above.

[0014] In a fourth aspect, an embodiment of the present application further provides a method for preparing a light-emitting device, the method comprising:

[0015] Providing a substrate and a functional ink, wherein the functional ink is prepared by using the composite material as described above, or by using a solution of the composite material prepared as described above;

[0016] preparing a first electrode on the substrate;

[0017] spraying functional ink on the first electrode, heating the sprayed functional ink to remove solvent and halogen in the functional ink, and forming a light-emitting layer;

[0018] A second electrode is prepared on the light-emitting layer.

[0019] Compared with the prior art, the embodiments of the present application have the following beneficial effects:

[0020] The composite material provided in the present application is formed by doping the organic material with halogen. When the halogen is used to form organic material nanoparticles, the agglomeration of the organic material nanoparticles can be inhibited. When the composite material is used to prepare the functional film layer of the light-emitting device, the performance of the light-emitting device can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the scheme in the present application, a brief introduction is given below to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0022] Figure 1 is a flow chart of a method for preparing a composite material solution provided in an embodiment of the present application;

[0023] Figure 2 is another flow chart of a method for preparing a composite material solution provided in an embodiment of the present application;

[0024] Figure 3 It is a flow chart of a method for preparing a light-emitting device provided in an embodiment of the present application. DETAILED DESCRIPTION

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, not to describe a specific order.

[0026] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0027] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.

[0028] The present application embodiment provides a composite material, which can be used to make a functional film layer of an organic light-emitting device; the composite material includes an organic material, and the organic material is doped with halogen. The organic material in this embodiment can be an organic semiconductor material, specifically a single material or a mixture of multiple materials, such as a single P-type organic semiconductor material or a single N-type organic semiconductor material, or an organic material obtained by mixing at least one P-type organic semiconductor material and at least one N-type organic semiconductor material. In this embodiment, the organic material is electrochemically P-type doped with halogen. Specifically, the doping of halogen will cause oxidation of the organic material (P-type doping), so that charge transfer occurs between the halogen and the organic material. Such P-type doping will promote the electrostatic repulsion between the formed organic material nanoparticles, so that the electrostatic repulsion of the organic material when forming nanoparticles increases, thereby inhibiting agglomeration and stabilizing the organic material nanoparticles. When the functional film layer of the organic light-emitting device is prepared by solution processing, the stable organic material nanoparticles are conducive to inkjet printing. At the same time, the doping of halogen is reversible for the oxidation of the organic material. After printing, the halogen is heated and removed to reduce the organic material to avoid affecting the functional film layer.

[0029] In this embodiment, the organic material may be selected from at least one of the following materials:

[0030] Oxadiazole, triazole, rhodamine, coumarins, 1,8-naphthalimide, pyrazoline, triphenylamine, porphyrin, carbazole, pyrazine, thiazole, rubrene, pentacene, triphenylamine, fullerene, phthalocyanine, cyanine, perylene and derivatives of the above materials, as well as polyaromatic ring polymers and copolymer polymers.

[0031] The composite material made of the above organic material has good photoelectric properties when making the functional film layer of the organic light-emitting device, wherein the oxadiazole can also be called oxadiazoles. The structure of oxadiazole is a heterocyclic five-membered ring with two carbon atoms, one oxygen atom, two nitrogen atoms and two double bonds. It is a class of heterocyclic aromatic compounds of the azole family, and the molecular formula is C2H2N2O, wherein the nitrogen atom exists at different positions in the oxadiazole ring. Based on the position, oxadiazole has four different possible isomers, such as 1,2,3-oxadiazole (a), 1,2,5-oxadiazole (b), 1,3,4-oxadiazine (c) and 1,2,4-oxatriazole (d), as follows:

[0032]

[0033] In addition, the polyaromatic ring polymer and copolymer polymer refer to polymers formed by polymerization.

[0034] Among them, the main macromolecular chain of polyaromatic ring polymers (aromatic heterocyclic polymers) is mainly composed of aromatic rings, heterocyclic rings or aromatic heterocyclic ring structures. In addition to carbon atoms, the ring atoms may also include oxygen atoms, sulfur atoms, nitrogen atoms and other atoms. Such structures can be formed by monomers containing heteroatoms during the polymerization process accompanied by a ring-closing reaction, or by polymerization of heterocyclic compounds containing reactive bifunctional groups, or by direct polymerization of aromatic rings. They are mainly stable five-membered heterocyclic and six-membered heterocyclic structures with aromatic or nearly aromatic properties; five-membered heterocyclic polymers include polyimides, polyoxadiazoles, polypyrroles, polypyrroles, polybenzoxazoles, polybenzothiazoles, polybenzimidazoles, polythiophenes, etc.; six-membered heterocyclic polymers include polyquinolines, polyquinoxalines, polytriazines, etc.

[0035] Copolymer polymers refer to polymers formed by two or more monomers participating in a polymerization reaction (called copolymerization). Because they contain two or more monomer units, this type of polymer is called a copolymer.

[0036] In this embodiment, the average particle size of the nanoparticles is 20 nm to 600 nm, and the specific surface area of ​​the nanoparticles is 20 m 2 / g~80m 2 / g. The average particle size of the nanoparticles is inversely proportional to the doping amount of halogen P-type doping.

[0037] In this embodiment, the mass ratio of the halogen to the organic material is (1:10) to (3:2). Under this mass ratio, the electrochemical P-type doping degree of the halogen to the organic material is appropriate, which is conducive to the reversible charge transfer between the halogen and the organic material. When the functional film layer is formed by inkjet printing, it is conducive to removing the halogen by heating, thereby obtaining a pure functional film layer and ensuring the performance of the organic light-emitting device.

[0038] In the present embodiment, the composite material further comprises a solvent having a dielectric constant of not less than 20, i.e., a solvent having a high dielectric constant, and the organic material doped with halogen forms organic material nanoparticles in the solvent. In the present embodiment, the solvent is an antisolvent, and the solubility of the organic material in the antisolvent is low. After the charge transfer between the halogen and the organic material, the antisolvent having a high dielectric constant helps to stabilize the charge and promote the separation of the counterions, which is conducive to the formation and maintenance of organic material nanoparticles. In the present embodiment, the solvent is selected from one or more of aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, alicyclic hydrocarbon compounds, halogenated hydrocarbon compounds, alcohol compounds, ether compounds, ester compounds, ketone compounds, acetonitrile, pyridine, and phenol.

[0039] In this embodiment, the halogen is one of iodine, fluorine, chlorine and bromine. The halogen in this embodiment is preferably iodine, which can be dissolved in a specific solvent (such as chloroform).

[0040] The following is an example of preparing a light-emitting layer of a light-emitting device by doping nanoparticles of organic material Mcp:TTSA with different proportions of iodine in P-type, and using the nanoparticle dispersion solution made of the composite material as ink, and the performance of the light-emitting device prepared by the composite material under different iodine P-type doping ratios is described in combination with the comparative example. The light-emitting device includes an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer and a cathode, and the specific device structure is ITO / PEDOT:PSS(35nm) / PVK(30nm) / Mcp:TTSA(35nm) / TPBi(40nm) / LiF(1nm) / Al(100nm).

[0041] Example 1

[0042] In an atmospheric environment, PEDOT:PSS was prepared on a pretreated ITO substrate (including an anode) by spin coating, and subjected to thermal annealing at 150°C for 15 min to form a hole injection layer; the substrate was then transferred into a nitrogen glove box, and then PVK was processed and thermally annealed at 100°C for 10 min to form a hole transport layer; a 35 nm light-emitting layer was then prepared by spin coating a 20 mg / mL Mcp:TTSA-based nanoparticle dispersion solution (wherein the iodine doping ratio was 10 wt %, equivalent to a mass ratio of iodine to organic material of 1:10), and the substrate was then placed on a hot stage at 120°C for annealing for 20 min to form a light-emitting layer; and then at 10 - 4 The electron transport layer, electron injection layer and cathode were formed by evaporating TPBi, LiF and Al in a vacuum below Pa, wherein LiF was deposited at a concentration of 0.05- The rate of evaporation is The rate of evaporation.

[0043] Example 2

[0044] In an atmospheric environment, PEDOT:PSS was prepared on a pretreated ITO substrate (including an anode) by spin coating, and subjected to thermal annealing at 150°C for 15 min to form a hole injection layer; the substrate was then transferred into a nitrogen glove box, PVK was then processed, and thermal annealing was performed at 100°C for 10 min to form a hole transport layer; a 35 nm light-emitting layer was then prepared by spin coating a 20 mg / mL Mcp:TTSA-based nanoparticle dispersion solution (wherein the iodine doping ratio was 50 wt%, equivalent to a mass ratio of iodine to organic material of 1:2); the substrate was then placed on a hot stage at 120°C for annealing for 20 min to form a light-emitting layer; and then at 10 - 4The electron transport layer, electron injection layer and cathode were formed by evaporating TPBi, LiF and Al in a vacuum below Pa, wherein LiF was deposited at a concentration of 0.05- The rate of evaporation is The rate of evaporation.

[0045] Example 3

[0046] In an atmospheric environment, PEDOT:PSS was prepared on a pretreated ITO substrate (including an anode) by spin coating, and subjected to thermal annealing at 150°C for 15 min to form a hole injection layer; the substrate was then transferred into a nitrogen glove box, and PVK was then processed and thermally annealed at 100°C for 10 min to form a hole transport layer; a 35 nm light-emitting layer was then prepared by spin coating a 20 mg / mL Mcp:TTSA-based nanoparticle dispersion solution (wherein the iodine doping ratio was 100 wt%, equivalent to a mass ratio of iodine to organic material of 1:1), and the substrate was then placed on a hot stage at 120°C for annealing for 20 min to form a light-emitting layer; and then at 10 - 4 The electron transport layer, electron injection layer and cathode were formed by evaporating TPBi, LiF and Al in a vacuum below Pa, wherein LiF was deposited at a concentration of 0.05- The rate of evaporation is The rate of evaporation.

[0047] Comparative Example 1

[0048] The ink used to prepare the light-emitting layer in Comparative Example 1 is also made based on a Mcp:TTSA solution. Different from the aforementioned Examples 1 to 3, the ink in Comparative Example 1 is prepared by dissolving the Mcp:TTSA solute in a chlorobenzene solvent at a concentration of 20 mg / ml. This is a conventional ink preparation method.

[0049] In an atmospheric environment, PEDOT:PSS was prepared on a pretreated ITO substrate (including an anode) by spin coating, and subjected to thermal annealing at 150°C for 15 min to form a hole injection layer; the substrate was then transferred into a nitrogen glove box, PVK was then processed, and thermal annealing was performed at 100°C for 10 min to form a hole transport layer; a 35 nm light-emitting layer was then prepared by spin coating a 20 mg / mL Mcp:TTSA chlorobenzene solution, and the substrate was then placed on a hot plate at 120°C for annealing for 20 min to form a light-emitting layer; and then the substrate was heated at 10 -4 The electron transport layer, electron injection layer and cathode were formed by evaporating TPBi, LiF and Al in a vacuum below Pa, wherein LiF was deposited at a concentration of 0.05- The rate of evaporation is The rate of evaporation.

[0050] Comparative Example 2

[0051] The ink used for preparing the light-emitting layer in Comparative Example 2 is also made based on the nanoparticle dispersion solution of Mcp:TTSA. Different from the aforementioned Examples 1 to 3, the iodine doping ratio in the nanoparticle dispersion solution based on Mcp:TTSA in Comparative Example 2 is 1 wt %, which is equivalent to a mass ratio of iodine to organic material of 1:100. This doping ratio is smaller than the doping ratio range of halogen in this embodiment.

[0052] Comparative Example 3

[0053] The ink used for preparing the light-emitting layer in Comparative Example 2 is also made based on the nanoparticle dispersion solution of Mcp:TTSA. Different from the aforementioned Examples 1 to 3, the iodine doping ratio in the nanoparticle dispersion solution based on Mcp:TTSA in Comparative Example 2 is 200wt%, which is equivalent to a mass ratio of iodine to organic material of 2:1. This doping ratio is higher than the doping ratio range of halogen in this embodiment.

[0054] For the light-emitting devices prepared in the above-mentioned embodiments 1 to 3 and comparative examples 1 to 3, the light-emitting performance parameters of each light-emitting device were tested by LED IVL testing equipment to obtain three parameters of the light-emitting device, namely, the luminous brightness Lmax (cd / m2), the current efficiency CE (cd / A) and the external quantum efficiency EQE (%), as shown in Table 1 below.

[0055] Table 1

[0056] <![CDATA[L max (cd / m 2 )]]> CE(cd / A) EQE(%) Example 1 1259 26.4 12.8 Example 2 1312 28.1 14.6 Example 3 1290 27.3 14.4 Comparative Example 1 1284 26.8 13.2 Comparative Example 2 187 2.2 0.8 Comparative Example 3 631 12.1 4.5

[0057] Among them, the luminous brightness Lmax (cd / m2): the luminous brightness of the device when the voltage loaded on both ends of the light-emitting device by the test equipment is 12V.

[0058] Current efficiency CE: the current efficiency of the light-emitting device at 1000 nit.

[0059] External quantum efficiency EQE (%): EQE is the ratio of the number of photons emitted by the light-emitting device per unit time to the electron-hole pairs injected into the light-emitting device by the test system per unit time. EQEmax is automatically tested by the test system.

[0060] The test results in Table 1 show that compared with the performance of the light-emitting device prepared by the ink prepared by the conventional method in Comparative Example 1, the composite material obtained by doping nanoparticles of organic material Mcp:TTSA with iodine in different proportions has better performance when the iodine doping concentration is high (Examples 2 and 3), and the light-emitting device prepared by preparing the nanoparticle dispersion solution as ink has better performance. This is because the organic material nanoparticle dispersion solution formed when the iodine doping concentration is high is more stable, which shows that the composite material provided in this embodiment is used to form a nanoparticle dispersion solution to prepare a light-emitting layer, which is a more effective method than the prior art. And considering that nanoparticles have a richer variety of choices in dispersing solvents, it is an efficient and flexible method for preparing light-emitting devices. Of course, in combination with Comparative Examples 2 and 3, when the iodine doping concentration is too low or too high, it will have a negative impact on the preparation of the light-emitting layer. In the case of low doping ratio in Comparative Example 2, the iodine content is too little to electrochemically p-type dope the organic material, and it is difficult to form stable nanoparticles, resulting in serious agglomeration and sedimentation, loss of photoelectric activity, and inability to prepare a good quality light-emitting film layer. In the case of ultra-high doping ratio in Comparative Example 3, the iodine content is too high, which also seriously reduces the final film quality of the organic material and affects the performance of the light-emitting device.

[0061] When preparing the functional film layer of the light-emitting device based on the above composite material, the two aspects that have the greatest impact on the performance of the functional film layer formed are the doping ratio of halogen and the heating temperature and time for heating to remove the halogen after spin-coating the ink. Specifically, in order to ensure the removal of halogen in the functional film layer, there are requirements for the heating temperature and time of the film layer based on different halogen types, among which the heating temperature of the fluorine-doped functional film layer is not less than 40°C and the time is not less than 5 minutes; the chlorine-doped film layer requires a heating temperature of not less than 60°C and a time of not less than 10 minutes; the bromine-doped film layer requires a heating temperature of not less than 80°C and a time of not less than 15 minutes; the iodine-doped film layer requires a heating temperature of not less than 100°C and a time of not less than 20 minutes.

[0062] The following describes the effects of different heating temperatures and times on the performance of the prepared light-emitting device when removing halogen doping at the same halogen P-type doping ratio with reference to the embodiments.

[0063] Example 4

[0064] The difference between this embodiment and embodiment 2 is that, in this embodiment, after spin coating the Mcp:TTSA-based nanoparticle dispersion solution with a concentration of 20 mg / mL, the substrate is placed on a hot plate for annealing at 100° C. for 20 minutes to form the final light-emitting layer.

[0065] Example 5

[0066] The difference between this embodiment and embodiment 2 is that, in this embodiment, after spin coating the Mcp:TTSA-based nanoparticle dispersion solution with a concentration of 20 mg / mL, the substrate is placed on a hot plate for annealing at 140° C. for 20 min to form the final light-emitting layer.

[0067] Example 6

[0068] The difference between this embodiment and embodiment 2 is that, in this embodiment, after spin coating the Mcp:TTSA-based nanoparticle dispersion solution with a concentration of 20 mg / mL, the substrate is placed on a hot plate for annealing at 160° C. for 20 min to form the final light-emitting layer.

[0069] Example 7

[0070] The difference between this embodiment and embodiment 2 is that, after spin coating the Mcp:TTSA-based nanoparticle dispersion solution with a concentration of 20 mg / mL, the substrate is placed on a hot plate at 120° C. for annealing for 40 minutes to form the final light-emitting layer.

[0071] Example 8

[0072] The difference between this embodiment and embodiment 2 is that, in this embodiment, after spin coating the Mcp:TTSA-based nanoparticle dispersion solution with a concentration of 20 mg / mL, the substrate is placed on a hot plate for annealing at 120° C. for 60 min to form the final light-emitting layer.

[0073] For the light-emitting devices prepared in the above embodiments 4 to 8, the light-emitting performance parameters of each light-emitting device were tested by LED IVL testing equipment to obtain three parameters of the light-emitting device: luminous brightness Lmax (cd / m2), current efficiency CE (cd / A) and external quantum efficiency EQE (%), as shown in Table 2 below.

[0074] Table 2

[0075] <![CDATA[L max (cd / m 2 )]]> CE(cd / A) EQE(%) Example 4 1263 26.5 13.1 Example 5 1420 30.7 16.7 Example 6 1271 26.6 13.4 Example 7 1539 31.8 17.3 Example 8 1392 28.6 15.0

[0076] By comparing the parameters of Examples 4 to 5 with those of Example 2, it is found that when the heating temperature is high, the photoelectric performance is better, while too low or too high a temperature will affect the photoelectric performance; by comparing the parameters of Examples 7 to 8 with Example 2, when the heating time is longer, the photoelectric performance is better, while too long or too short a heating time will affect the photoelectric performance, especially too long a heating temperature and heating time will have an adverse effect on the functional film layer morphology and molecular stacking morphology, etc., which is not conducive to the performance of the light-emitting device.

[0077] The composite material provided in the present application achieves P-type doping of organic materials by doping halogens into organic materials. When forming organic material nanoparticles, the electrostatic repulsion of organic material nanoparticles can be promoted and agglomeration can be inhibited. When used in the preparation of light-emitting devices, it is beneficial to inkjet printing and processing of functional film layers of light-emitting devices, thereby improving the performance of light-emitting devices.

[0078] The present application also provides a method for preparing a composite material solution. Figure 1 As shown, the method includes:

[0079] S101, mixing an organic material with a first solvent to obtain a first solution.

[0080] Specifically, the first solvent can be a good solvent (such as chloroform) that can effectively dissolve organic materials. At least one organic material is mixed with the first solvent to dissolve the organic material in the first solvent to obtain a first solution of a certain concentration (the concentration can be set as needed). During the dissolution of the organic material, heating and stirring can be performed to accelerate the dissolution. When dissolving at least two organic materials, each organic material can be mixed with the first solvent separately to obtain at least two solutions, and then these solutions are mixed to obtain the first solution.

[0081] S102, dissolving the halogen element in a second solvent to obtain a second solution containing the halogen.

[0082] Wherein, after the halogen element is dissolved in the second solvent, the predetermined time is maintained to ensure that the dissolution is complete and stable. In this embodiment, the first solvent and the second solvent may be the same solvent, such as chloroform. In another embodiment, the first solvent and the second solvent are different solvents that are mutually soluble, as long as they are solvents for organic materials and halogens.

[0083] The halogen element may be one of iodine, fluorine, chlorine and bromine, with iodine being preferred.

[0084] S103, mixing the first solution and the second solution to obtain an organic material solution doped with halogen.

[0085] In this step, the first solution and the second solution can be mixed in proportion to achieve P-type doping of the organic material by the halogen, thereby completing the preparation of the halogen-doped organic material solution. To ensure the effective removal of the subsequent halogen, in this embodiment, the mass ratio of the halogen to the organic material is (1:10) to (3:2). The halogen doped in this step can be used as a stabilizer for the subsequent organic material nanoparticles.

[0086] S104, mixing the organic material solution and a third solvent to obtain a solution of the composite material.

[0087] In this embodiment, the function of the third solvent is to reduce the solubility of the organic material. For this purpose, the third solvent uses an anti-solvent with a dielectric constant of not less than 20, that is, an anti-solvent with a high dielectric constant, such as acetonitrile. The solubility of the organic material in the anti-solvent is low. When the organic material solution is mixed with the anti-solvent with a high dielectric constant, the reduction in the solubility of the organic material leads to the precipitation of organic material nanoparticles that are quickly formed. Due to the electrochemical P-type doping of the organic material by the halogen, the electrostatic repulsion of the organic material nanoparticles is promoted, and agglomeration is suppressed, thereby forming a stable dispersion of organic material nanoparticles. In this embodiment, in the process of mixing the organic material with the third solvent, vigorous stirring can be performed to accelerate the formation of organic material nanoparticles.

[0088] After the dispersion of organic material nanoparticles is formed, the charge transfer occurs between the halogen and the organic material, and the antisolvent with a high dielectric constant helps to stabilize the charge and promote the separation of counter ions, which is beneficial to maintaining the stability of the dispersion of organic material nanoparticles.

[0089] In another embodiment, if Figure 2 As shown, based on the above steps, after obtaining a solution of the composite material, the method further comprises:

[0090] S105, heating the solution of the composite material to remove part of the solvent.

[0091] Among them, the removed solvents are mainly the first solvent and the second solvent. In order to ensure the effective removal of the first solvent and the second solvent, in this embodiment, the boiling point of the third solvent needs to be higher than the first solvent and the second solvent, for example, the boiling point of acetonitrile is higher than that of chloroform.

[0092] S106, centrifuging the composite material solution after removing part of the solvent to remove aggregates in the solution, thereby obtaining a third solution, wherein stable organic material nanoparticles are dispersed in the third solution.

[0093] As the solvent is removed from the solution of the halogen-doped composite material in step S105, the concentration may increase and there may be sediment impurities such as agglomerates. In this step, the solution of the composite material after the concentration is increased in step S105 is centrifuged to remove sediment impurities such as agglomerates to obtain a third solution containing a stable dispersion of organic material nanoparticles, that is, a solution of a composite material with stable properties.

[0094] The process of the above steps S101 to S106 is illustrated below with a specific example.

[0095] P-type organic semiconductor PM6 [CAS No. 1802013-83-7, molecular formula (C 68 H 76 F2O2S8)n ] and N-type organic semiconductor BTP-eC9 (CAS No. 2598965-39-8, molecular formula C 86 H 94 Cl4N8O2S5) were dissolved in chloroform at a concentration of 4 g / L, heated to 45°C and stirred for 20 minutes to obtain two solutions, which were then mixed in equal volumes to form a bulk heterojunction mixed solution with a total concentration of 4 g / L, i.e., the first solution.

[0096] Iodine was then dissolved in chloroform at a concentration of 10 g / L and maintained for 1 hour to obtain a chloroform solution of iodine, ie, the second solution.

[0097] Then, 1.6 mL of the iodine chloroform solution (second solution) was added to 10 mL of the bulk heterojunction mixed solution (first solution), and then 8.4 mL of chloroform solvent was added to the mixed solution to dilute the solution to obtain a halogen-doped organic material solution with a concentration of 2 g / L.

[0098] Under vigorous stirring, 1 mL of a 2 g / L halogen-doped organic material solution was injected into 7 mL of acetonitrile within 0.8 seconds, and then heated at 70°C until the chloroform was removed and part of the acetonitrile was volatilized, and the concentration of the halogen-doped organic material solution increased.

[0099] Finally, the halogen-doped organic material solution with increased concentration is placed in a centrifugal device for centrifugal treatment to remove agglomerates in the solution to obtain a stable organic material nanoparticle dispersion, that is, the solution of the composite material.

[0100] The method for preparing a composite material solution provided in the present application introduces halogen as a reversible electrochemical P-type dopant of an organic material and uses a solvent with a high dielectric constant as an antisolvent to prepare a stable dispersion of nanoparticles of an organic material. The method is simple to implement and effectively avoids the introduction of impurities such as surfactants in the preparation process of a conventional dispersion of nanoparticles of an organic material, simplifies the steps, and facilitates mass production. After obtaining a dispersion of stable nanoparticles of an organic material doped with halogen, it is made into an ink that can meet the performance requirements of a functional film layer of an inkjet printing light-emitting device.

[0101] An embodiment of the present application also provides a light-emitting device, which includes a first electrode, a second electrode and a light-emitting layer; the light-emitting layer is arranged between the first electrode and the second electrode, and the light-emitting layer is prepared based on the composite material described in the above embodiment, or based on the solution of the composite material prepared according to the preparation method of the solution of the composite material in the above embodiment.

[0102] In this embodiment, the light-emitting device also includes a hole injection layer, a hole transport layer, an electron transport layer and an electron injection layer; wherein the first electrode is an anode, the second electrode is a cathode, the hole injection layer and the hole transport layer are stacked between the first electrode and the light-emitting layer, and the electron transport layer and the electron injection layer are stacked between the second electrode and the light-emitting layer.

[0103] In this embodiment, the material of the first electrode and / or the second electrode includes one or more of metal, carbon material and metal oxide, the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes doped or undoped metal oxide, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2.

[0104] In this embodiment, the material of the electron transport layer and / or the electron injection layer includes inorganic materials and / or organic materials; the inorganic material is selected from one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped elements include one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material is selected from one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds.

[0105] In this embodiment, the material of the hole transport layer and / or the hole injection layer includes at least one of TFB, CuPc, PVK, Poly-TPD, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, TAPC, MCC, F4-TCNQ, HATCN, 4,4',4'-tri(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tinides, doped graphene, undoped graphene and C60.

[0106] The light-emitting device provided in the present application can effectively improve the performance of the light-emitting device by preparing ink using the composite material of the above embodiment, or by preparing ink using a solution of a composite material prepared by the method for preparing a solution of the composite material in the above embodiment, to prepare the light-emitting layer of the light-emitting device.

[0107] The present application also provides a method for preparing a functional film layer of an organic light-emitting device, such as Figure 3 As shown, the method includes:

[0108] S201. Provide a substrate and a functional ink, in which halogen-doped organic material nanoparticles are dispersed; specifically, the functional ink is prepared using the composite material described in the above embodiment, or is prepared based on a solution of a composite material prepared according to the method for preparing a solution of the composite material in the above embodiment.

[0109] S202, preparing a first electrode on the substrate.

[0110] S203, spraying functional ink on the first electrode, heating the sprayed functional ink, removing the solvent and halogen in the functional ink, and forming a light-emitting layer.

[0111] Among them, after the printing spraying is completed, the printed ink is allowed to deposit for a certain time to deposit the nanoparticles, and the substrate is heated at a certain temperature for a set time, such as heating the substrate at 120°C for 10 minutes to heat the deposited functional ink. During the heat treatment process, the third solvent, the halogen, and the residual first solvent and the second solvent can be removed to form an undoped light-emitting layer.

[0112] S204, preparing a second electrode on the light-emitting layer.

[0113] In this embodiment, as long as the halogen has an appropriate degree of electrical P-type doping on the organic material nanoparticles, the charge transfer between it and the organic material nanoparticles is reversible. The halogen can be removed by a simple heat treatment process on the light-emitting layer to achieve dedoping and leave a pure organic material film layer.

[0114] In other embodiments, the light-emitting device may have other functional film layers in addition to the light-emitting layer, such as a hole injection layer, a hole transport layer, an electron transport layer and an electron injection layer. Specifically, the method for preparing the light-emitting device, before preparing the light-emitting layer, further includes sequentially preparing a hole injection layer and a hole transport layer on the first electrode, and then preparing the light-emitting layer on the hole transport layer; then sequentially preparing an electron transport layer and an electron injection layer on the light-emitting layer, and finally preparing a second electrode on the electron injection layer. When preparing the hole injection layer, the hole transport layer, the electron transport layer and the electron injection layer, the main material and the guest material of these functional film layers may also be P-type doped with halogen to prepare a composite material or a solution of the composite material in the above embodiment, and then the functional ink is used to prepare the corresponding functional film layer by inkjet printing, and the performance of the light-emitting device obtained thereby can be significantly improved. Those skilled in the art can select organic materials according to actual needs and make them into composite materials doped with halogen, and obtain organic light-emitting devices with different functional film layers by the above method.

[0115] The method for preparing a light-emitting device provided in the present application uses the composite material described in the above embodiment, or ink made from a solution of the composite material prepared by the method for preparing a solution of the composite material in the above embodiment to prepare a functional film layer of the light-emitting device. Since the halogen in the ink can be completely removed by heat treatment, a pure functional film layer is formed, thereby effectively improving the performance of the light-emitting device.

[0116] Obviously, the embodiments described above are only some embodiments of the present application, rather than all embodiments. The preferred embodiments of the present application are given in the accompanying drawings, but they do not limit the patent scope of the present application. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the specification and drawings of this application, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of this application.

Claims

1. A composite material, characterized in that: The composite material includes an organic material doped with a halogen.

2. The composite material according to claim 1, characterized in that The mass ratio of the halogen to the organic material is (1:10) to (3:2).

3. The composite material according to claim 1 or 2, characterized in that: The composite material further includes a solvent having a dielectric constant of not less than 20.

4. The composite material according to claim 3, characterized in that The solvent is selected from one or more of aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, alicyclic hydrocarbon compounds, halogenated hydrocarbon compounds, alcohol compounds, ether compounds, ester compounds, ketone compounds, acetonitrile, pyridine, and phenol.

5. The composite material according to claim 1 or 2, characterized in that: The average particle size of the nanoparticles is 20 nm to 600 nm; and / or The specific surface area of ​​the nanoparticles is 20 m 2 / g~80m 2 / g.

6. The composite material according to claim 1 or 2, characterized in that: The organic material is selected from at least one of the following materials: Oxadiazole, triazole, rhodamine, coumarins, 1,8-naphthalimide, pyrazoline, triphenylamine, porphyrin, carbazole, pyrazine, thiazole, rubrene, pentacene, triphenylamine, fullerene, phthalocyanine, cyanine, perylene and derivatives of the above materials, as well as polyaromatic ring polymers and copolymer polymers.

7. A method for preparing a composite material solution, characterized in that: The method comprises: mixing an organic material with a first solvent to obtain a first solution; Dissolving a halogen element in a second solvent to obtain a second solution containing the halogen; mixing the first solution and the second solution to obtain an organic material solution doped with halogen; The organic material solution and a third solvent are mixed to obtain a solution of the composite material.

8. The method for preparing a composite material solution according to claim 7, characterized in that: After obtaining the composite material solution, the method further comprises: heating the solution of the composite material to remove part of the solvent; The composite material solution after removing part of the solvent is centrifuged to remove agglomerates in the solution to obtain a third solution in which stable organic material nanoparticles are dispersed.

9. The method for preparing a composite material solution according to claim 8, characterized in that: The first solvent and the second solvent are the same solvent; or The first solvent and the second solvent are different solvents that are miscible with each other.

10. The method for preparing a composite material solution according to claim 8, characterized in that: The mass ratio of the halogen to the organic material is (1:10) to (3:2).

11. The method for preparing a composite material solution according to claim 8, characterized in that: The dielectric constant of the third solvent is not less than 20.

12. The method for preparing a composite material solution according to any one of claims 7 to 11, characterized in that: The third solvent has a boiling point higher than the boiling points of the first solvent and the second solvent.

13. A light emitting device, characterized in that: The light emitting device comprises: a first electrode and a second electrode; A light-emitting layer is disposed between the first electrode and the second electrode, wherein the light-emitting layer is prepared based on the composite material according to any one of claims 1 to 7, or is prepared based on a solution of the composite material prepared according to any one of claims 8 to 13.

14. The light emitting device according to claim 13, characterized in that: The light emitting device further comprises: A hole injection layer and a hole transport layer, wherein the hole injection layer and the hole transport layer are stacked between the first electrode and the light-emitting layer; An electron transport layer and an electron injection layer, wherein the electron transport layer and the electron injection layer are stacked between the second electrode and the light emitting layer.

15. The light emitting device according to claim 14, characterized in that: The material of the first electrode and / or the second electrode includes one or more of metal, carbon material and metal oxide, the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes doped or undoped metal oxide, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or The material of the electron transport layer and / or the electron injection layer includes inorganic materials and / or organic materials; the inorganic material is selected from one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped elements include one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material is selected from one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds; and / or The material of the hole transport layer and / or the hole injection layer includes at least one of TFB, CuPc, PVK, Poly-TPD, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, TAPC, MCC, F4-TCNQ, HATCN, 4,4',4'-tris(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tinides, doped graphene, undoped graphene and C60.

16. A method for preparing a light emitting device, characterized in that: The method comprises: Providing a substrate and a functional ink, wherein the functional ink is prepared by using the composite material according to any one of claims 1 to 6, or by using a solution of the composite material prepared according to any one of claims 7 to 12; preparing a first electrode on the substrate; spraying functional ink on the first electrode, heating the sprayed functional ink to remove solvent and halogen in the functional ink, and forming a light-emitting layer; A second electrode is prepared on the light-emitting layer.